DIRECTIVE SPEECH ACT IN KEAJAIBAN TOKO KELONTONG NAMIYA BY KEIGO HIGASHINO - Velini, Riskia Sitti; Chandra, Oktiva Herry (Universitas PGRI Sumatera Barat, 2023)
The purpose of this study is to identify and discuss the types of directive speech act found in the novel Keajaiban Toko Kelontong Namiya (KTKN). This study is descriptive qualitative research, in which the data are in forms of words. The researcher used Pragmatics approach in analyzing the data, particularly speech act theory by Searle. The source of data is the utterances made by the characters in the novel KTKN and data were obtained by using non-participant observation method. In addition, note-taking was used as the advanced technique to take notes of utterances that used directive speech act. The result of this study shows that there are four types of directive speech act used by the characters in KTKN novel, namely ask (to), advise, warn and beg. The most used type is ask (to) with 35 utterances (50.72%). Then it is followed by directive speech act type advise with 23 utterances (33.34%), warn with 10 utterances (14,5%) and lastly beg type with 1 utterance (1.44%). Ask (to) as the most used directive speech act is influenced by the role of the characters Mr. Namiya, Atsuya, Kohei and Shota as the person who were trying to help people by giving advice and offering a solution to their problems. They tend to help people by asking them to take an action and the utterances with directive speech act type act (to) that they used are marked by the phrases with performative verbs like silakan, jadi berhentilah. coba lihat, tolong and lakukan.